2015
DOI: 10.1007/s00376-015-4246-0
|View full text |Cite
|
Sign up to set email alerts
|

A diagnostic study of the asymmetric distribution of rainfall during the landfall of typhoon Haitang (2005)

Abstract: The precipitation during landfall of typhoon Haitang (2005) showed asymmetric structures (left side/right side of the track). Analysis of Weather Research and Forecasting model simulation data showed that rainfall on the right side was more than 15 times stronger than on the left side. The causes were analyzed by focusing on comparing the water vapor flux, stability and upward motion between the two sides. The major results were as follows: (1) Relative humidity on both sides was over 80%, whereas the converg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…Figure 12 shows that high rainfall rates occurred on the left side of Typhoon Sarika's track. Many studies have shown that the remarkable asymmetric TC rainfall distribution is caused by the vertical wind shear, tropical cyclones motion, and water vapor flux or topography, in which the vertical wind shear is the primary factor [46][47][48][49][50][51][52][53]. Moreover, the rainfall maximum in the inner-core region of a TC is always located on the downshear left side for TCs in the Northern Hemisphere regardless of the storm motion and shear orientation [52,53].…”
Section: Temperature Responsementioning
confidence: 99%
“…Figure 12 shows that high rainfall rates occurred on the left side of Typhoon Sarika's track. Many studies have shown that the remarkable asymmetric TC rainfall distribution is caused by the vertical wind shear, tropical cyclones motion, and water vapor flux or topography, in which the vertical wind shear is the primary factor [46][47][48][49][50][51][52][53]. Moreover, the rainfall maximum in the inner-core region of a TC is always located on the downshear left side for TCs in the Northern Hemisphere regardless of the storm motion and shear orientation [52,53].…”
Section: Temperature Responsementioning
confidence: 99%
“…The leading factors which have a significant impact on both the amount and distribution of rainfall associated with landfalling TCs are the following: (a) TC intensity, (b) TC distance to the station, and (c) TC azimuth relative to the station, respectively (Dominguez & Magaña, 2018;Yu & Wang, 2018;Yue et al, 2015). The high intensity TC type mostly appears along the coastline and gradually decreases toward the inland areas.…”
Section: Methodsmentioning
confidence: 99%
“…All rights reserved. Yue et al, 2015). The high intensity TC type mostly appears along the coastline and gradually decreases towards the inland areas.…”
Section: Accepted Articlementioning
confidence: 96%
See 1 more Smart Citation
“…There are substantial discrepancies between the different regions affected by TCP over China due to the complex terrain and various climate characteristics (Yue et al, 2015;Qiu et al, 2019). Previous studies have pointed out that mountainous terrain can increase the intensity of TCP (Jiang et al, 2018;Chen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%